An Update on the Status of Vaccine Development for SARS-CoV-2 Including Variants. Practical Considerations for COVID-19 Special Populations. (February 2022) - Kantarcioglu, Bulent; Iqbal, Omer; Lewis, Joseph; Carter, Charles A.; Singh, Meharvan; Lievano, Fabio; Ligocki, Mark; Jeske, Walter; Adiguzel, Cafer; Gerotziafas, Grigoris T.; Fareed, Jawed
The progress in the development of various vaccine platforms against SARS-CoV-2 have been rather remarkable owing to advancement in molecular and biologic sciences. Most of the current vaccines and those in development focus on targeting the viral spike proteins by generating antibodies of varying spectrum. These vaccines represent a variety of platforms including whole virus vaccines, viral vector vaccines, nucleic acid vaccines representing RNA, DNA, and their hybrid forms. The therapeutic efficacy of these vaccines varies owing to their pharmacodynamic individualities. COVID-19 variants are capable of inducing different pathologic responses and some of which may be resistant to antibodies generated by current vaccines. The current clinical use of these vaccines has been through emergency use authorization until recently. Moreover, the efficacy and safety of these vaccines have been tested in substantial numbers of individuals but studies in special populations that better reflect the global population are pending results. These specialized populations include young children, immunocompromised patients, pregnant individuals, and other specialized groups. Combination approaches, molecularly modified vaccination approaches, and vaccines conferring longer periods of immunity are being currently being investigated, as well as pharmacovigilance studies. The continual transformation of SARS-CoV-2 and its variants are of concern along with the breakthrough infections. These considerations pose new challenges for the development of vaccination platforms. For this purpose, booster doses, combination vaccine approaches, and other modalities are being discussed. This review provides an updated account of currently available vaccines and those in advanced development with reference to their composition and mechanisms of action. A discussion on the use of vaccines in special populations including immunocompromised patients, pregnant women and other specialized populations are also included.